Teologi Transformatif Pemikiran Moeslim Abdurrahman - Moh. Arif Afandi (Refleksi: Jurnal Filsafat dan Pemikiran Keislaman, 2021)
This article explains transformative theology according to Moeslim Abdurrahman. In essence, theology is not only a problem with God but is closely related to social problems. The assumption that the scope of theology is only in the vertical realm requires a more serious review because this is a very narrow view. Theology should provide space to pay attention to social conditions in society, to see social inequality, injustice, and oppression. Then proceed to read the social structure critically, to find the cause of the social problem. The re-reading of Islamic theology is carried out so that it remains relevant to the times, able to solve existing social problems. This research is a literature study using qualitative methods, to analyze the data using an interpretation method, while the approach uses a social approach. The results of this research are the essence of transformative theology according to Moeslim Abdurrahman, the methods of transformative theology, and the goals of transformative theology.